Webinar Strategi Pergantian Pemain untuk Pelatih Bola Voli dengan Aplikasi Zoom Meeting - Sujarwo - Sujarwo (Universitas Pendidikan Indonesia Kampus Purwakarta, 2021)
This community service aims to provide additional information and increase the knowledge possessed by volleyball coaches in Indonesia about changing players in volleyball games. The service method uses video conferencing with the zoom meeting application; the service will be held on May 5, 2021. The number of participants in this activity is 44 trainers with two speakers. The service time in the interactive discussion is 180 minutes. It consists of 80 minutes of material presentation and 100 minutes of question and answer or discussion. The instrument determines the increase in the trainer's knowledge about the service material by using test questions with the Google form application. The trainer's response results were analyzed with the difference in the mean of the pre and post-test results. The pre-test of volleyball coach knowledge in the average score: 61.62 after following the material for community service from the presenters, the post-test results showed an increase in the average score, namely: 76.74. This average value has exceeded the target of the service, which is an average value of 75. This community service has a positive impact on the coach's knowledge about substituting players, by 15% calculated from the increase in the average score multiplied by 100%. The conclusion is that the knowledge of the coach in making substitutions, and the coach's courage in changing star players for the sake of the team, is a characteristic of the profession of a volleyball coach.